2020
DOI: 10.3389/fphar.2020.555475
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Complications of Prostate Cancer Treatment

Abstract: Treatment of prostate cancer (PC) is a rapidly evolving field of pharmacology research. In recent years, numerous novel therapeutics that improve survival and ameliorate disease control have been approved. Currently, the systemic treatment for prostate neoplasm consists of hormonal therapy, chemotherapy, immunotherapy, radiopharmaceuticals, targeted therapy, and supportive agents (e.g., related to bone health). Unfortunately, many of them carry a risk of cardiovascular complications, which occasionally pose a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 86 publications
1
19
0
2
Order By: Relevance
“…The rationale regarding the association between ADT and end organ adverse events came from consequences stemming from androgen receptor blockade. Androgen receptor mediated metabolic responses act as an important driver towards maintaining both physical and mental health in men [ 5 , 15 , 16 ]. Several cohort and cross section studies have shown an association between lower serum testosterone (a principal male sex hormone which binds to the androgen receptor) levels and a higher metabolic syndrome percentage and cardiovascular morbidity [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rationale regarding the association between ADT and end organ adverse events came from consequences stemming from androgen receptor blockade. Androgen receptor mediated metabolic responses act as an important driver towards maintaining both physical and mental health in men [ 5 , 15 , 16 ]. Several cohort and cross section studies have shown an association between lower serum testosterone (a principal male sex hormone which binds to the androgen receptor) levels and a higher metabolic syndrome percentage and cardiovascular morbidity [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…АГ и СД в сочетании с химиотерапией значительно повышают риск развития таких неблагоприятных сердечно-сосудистых событий, как инсульт, инфаркт миокарда и застойная сердечная недостаточность [13]. При раке предстательной железы также часто имеют место ССЗ, которые могут прогрессировать в ходе андрогендепривационной терапии [14]. Риск смерти от ССО у пациентов с ЗНО предстательной железы превышает аналогичный риск в общей популяции в 4-6 раз [15].…”
Section: цель консультацииunclassified
“…Increased vascular tone Decreased activation of nitric oxide synthase in endothelial cells [33,34] Decreased downregulation of L-type voltage-gated calcium channels and decreased upregulation of calcium-activated potassium channels on vascular smooth muscle cells [35,36] Vascular remodeling Increased intima--media thickness [37,38] Increased vascular calcification [35,38,39] Decreased antisenescence effect of testosterone [40] Systemic inflammation and atherosclerosis lesion formation The risk of cardiac events appears to be related to duration of treatment, with one trial demonstrating a 6% increase in number of cardiac events associated to long-term treatment (28 months; 20%) as opposed to short-term (4 months; 14%) [52].…”
Section: Vascular Effects Pathophysiologymentioning
confidence: 99%